Artistic Practices of Vitaly Komar and Alexander Melamid: From Production to Media - Svetlyakov, Kirill A. (Actual Problems of Theory and History of Art, 2018)
There was a tectonic fracture between late modernism and emerging post-modernism in non-official Soviet art at the turn of the 1960s — 1970s. Instead of traditional works of art, such as paintings and sculptures, Vitaly Komar and Alexander Melamid, as well as some other artists, invented the non-exhibitable forms of art and created the works intended to exist only in the descriptions and photographs published by media. The birth of an artistic performance was stimulated by political events, such as the protest actions of the Jews who were denied immigration from the USSR, the ban on the exhibition of non-official art. A political statement was inseparable from an artistic one in the practice of socialist art representatives. However, a product of non-official art could mimic official propaganda. The article examines the genealogy of non-official art in the context of the crisis of social, political, and artistic processes in Soviet culture, which gradually dissolved during the transferring to postmodernism. Herewith, the violation and destruction of the autonomy of art was incorporated in the program of the Soviet cultural project.
Keywords: Vitaliy Komar; Alexander Melamid; Sots Art; conceptualism; unofficial Soviet art; postmodernism; performance